Edukasi Berbasis Al-Qur'an dan Hadis untuk Membangun Kesadaran Perempuan tentang Ketenangan Jiwa dalam Keluarga: Al-Qur'an and Hadith-Based Education to Build Women's Awareness of Peace of Mind Within the Family - Ulfah Zakiyah; Falika Nahwa Rosyawaly; Leni Wahyuni Lubis (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
The emotional well-being of women as wives and mothers is a fundamental pillar in building safe and harmonious families. In Bakung Village, Kronjo Subdistrict, Tangerang Regency, preliminary observations and interviews with community leaders revealed that most young mothers lacked adequate understanding of the concept of women’s inner peace from an Islamic perspective, particularly as derived from the Qur’an and Hadith. Women tended to perceive inner peace as an individual responsibility rather than a shared value to be cultivated collectively within family relationships. This community service activity aimed to improve the understanding of young mothers in Bakung Village regarding the concept of women’s inner peace based on the Qur’an and Hadith as a foundation for building safe families. The activity was conducted through interactive lectures, group discussions, and structured reflection sessions at Mushola Daarussalam, involving 27 participants. Evaluation was carried out through structured observation and reflective discussions guided by open-ended questions. The results demonstrated a meaningful shift in participants’ perspectives: they began to understand that Islam honors women and places their inner peace as a fundamental objective of marriage, and became aware that husbands and all family members share collective responsibility in nurturing that peace. This activity contributed to strengthening the community’s religious literacy and is recommended to be continued with more varied participatory approaches.